Pax7 is required for establishment of the xanthophore lineage in zebrafish embryos - Nord, Hanna (Mol Biol Cell, 2016)
The pigment pattern of many animal species is a result of the arrangement of different types of pigment-producing chromatophores. The zebrafish has three different types of chromatophores: black melanophores, yellow xanthophores, and shimmering iridophores arranged in a characteristic pattern of golden and blue horizontal stripes. In the zebrafish embryo, chromatophores derive from the neural crest cells. Using pax7a and pax7b zebrafish mutants, we identified a previously unknown requirement for Pax7 in xanthophore lineage formation. The absence of Pax7 results in a severe reduction of xanthophore precursor cells and a complete depletion of differentiated xanthophores in embryos as well as in adult zebrafish. In contrast, the melanophore lineage is increased in pax7a/pax7b double-mutant embryos and larvae, whereas juvenile and adult pax7a/pax7b double-mutant zebrafish display a severe decrease in melanophores and a pigment pattern disorganization indicative of a xanthophore- deficient phenotype. In summary, we propose a novel role for Pax7 in the early specification of chromatophore precursor cells.